Açude Grande of Cajazeiras-PB: an analysis of its water and its uses - Souza Júnior, Teobaldo Gabriel de (2020)
In Brazil, the northeast region has the second largest population and the least water volume in the country, although exhibit several negligences regarding such precious element. The Epitácio Pessoa Senator Lake, locally known as “Big Lake”, is located in Cajazeiras city, at Paraiba state, one of the 1,262 cities in the semiarid region. This open air reservoir, which was rebuilt by the federal government during the 1915 drought, is, now a days, found degraded due to direct launch of non-treated effluents. Thus, the current work proposed: to investigate the historic evolution of its deterioration aiming to establish relationship between the urbanization growth and the loss of its superficial water quality. Therefore was realized, in the rainy and dry seasons of 2019: evaluation of reservoir condition by means of 15 limnological variables; application of the Trophic Status Index; and it was inferred about its decline using techniques of geoprocessing and Remote Sensing. It was also carried out 71 interviews aiming to verify how the population and the public authorities currently sense and deal with the reservoir. As results it was observed: currently the lake is found eutrophic; the fast urban growth influenced in the historic degradation; the urban population, though is conscious about the loss of water quality due to hostile urbanization and recognizes the importance of the water for the region, appear to know little about its historical value and thus do not feel responsible enough to act toward its revitalization; the local public authority currently is trying to reverse the notorious disdain regarding the big lake; the lake did not yet reached its critical and irreversible point, though it is close to that, it can yet be recovered, what may give grounds for a possible requalification in the future.